2007
DOI: 10.1007/s10792-007-9169-z
|View full text |Cite
|
Sign up to set email alerts
|

FACT contrast sensitivity as a diagnostic tool in glaucoma

Abstract: Both the presence of a significant difference between the CS of glaucoma patients and control subjects and a high specificity of contrast sensitivity suggests that the FACT test may be used as a tool for diagnosis of patients with glaucoma, besides other methods such as short-wavelength automated perimetry (SWAP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 25 publications
2
37
1
4
Order By: Relevance
“…Although visual acuity was good, the CS of the eyes with glaucoma was significantly less than among healthy subjects except at 1.5 cpd (p<0.012). This result was compatible with that previously reported by Onal et al (7) using the FACT wall chart. The authors suggested that the FACT chart was useful for early diagnosis of patients with glaucoma, accompanied by a short-wavelength automated perimetry.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Although visual acuity was good, the CS of the eyes with glaucoma was significantly less than among healthy subjects except at 1.5 cpd (p<0.012). This result was compatible with that previously reported by Onal et al (7) using the FACT wall chart. The authors suggested that the FACT chart was useful for early diagnosis of patients with glaucoma, accompanied by a short-wavelength automated perimetry.…”
Section: Discussionsupporting
confidence: 94%
“…CS is an important part of functional vision that is related to many activities of daily living and measuring it is one of the best ways to assess vision quality (3)(4)(5) . Despite having normal visual acuity measured by a Snellen chart, the satisfaction with the results of refractive surgery may vary relative to CS, and some eye diseases cause isolated loss of CS (4,(6)(7)(8) . Snellen acuity tests have a limited ability to detect fine changes in contrast because high contrast letters (black on white) are used (9) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 A recent study has been conducted to investigate spatial-contrast sensitivity (CS) assessment as a tool for diagnosis of early glaucoma in patients with good visual acuity. 38 It was found that both the presence of a significant difference between the CS of glaucoma patients and control subjects and a high specificity of contrast sensitivity suggests that the FACT test may be used as a tool for diagnosis of patients with glaucoma, besides other methods such as short-wavelength automated perimetry (SWAP). 38 …”
Section: A E Omoti and Associates Diagnosis Of Primary Open Angle Gmentioning
confidence: 99%
“…38 It was found that both the presence of a significant difference between the CS of glaucoma patients and control subjects and a high specificity of contrast sensitivity suggests that the FACT test may be used as a tool for diagnosis of patients with glaucoma, besides other methods such as short-wavelength automated perimetry (SWAP). 38 …”
Section: A E Omoti and Associates Diagnosis Of Primary Open Angle Gmentioning
confidence: 99%